ANALISIS KOMUNIKASI, KOMITMEN ORGANISASI DAN INSENTIF TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN PATTALLASSANG KABUPATEN GOWA - Jumarti; Tiblola, Jordan; Irwandi, Syahrul; Sudirman (Jurnal Unicorn ADPERTISI, 2024)
The purpose of this study was to determine and analyze the influence of communication, organizational, commitment, and incentives to employee performance at the District Office PattallassangGowa district, as well as to determine the dominant factor. The study population was all employees at the District Office PattallassangGowa totaling 34 people. Because the population is small or less than 100 people, the entire population is used as a sample or samples of 100%. The analytical method used is multiple linear regression analysis. The results showed that communication, organizational commitment, and positive and significant incentives either partially or simultaneously on employee performance Pattallassang Gowa District Office, where the incentive factor is the most influential factor.